Case report: Prader–Willi syndrome and inflammatory arthritis—An important consideration - Marelli, Luca; Dallos, Tomáš; Miserocchi, Elisabetta; Nucci, Paolo; Tombolini, Beatrice; De Lucia, Orazio; Gattinara, Maurizio; Caporali, Roberto; Marino, Achille (Frontiers in Pediatrics, 2023)
Background: Prader-Willi syndrome (PWS) is a multisystemic genetically determined disorder. Musculoskeletal manifestations are common in most patients. We report the cases of two children with PWS who developed inflammatory arthritis, complicated with chronic anterior bilateral uveitis, in one case. To our knowledge, there have been no previous reports of such association. Case presentation: Case 1. A 3-year-old girl diagnosed with PWS developed arthritis of the right knee with morning stiffness, joint swelling, and limited range of motion. Other causes of arthritis were ruled out. Increased inflammatory markers, antinuclear antibodies (ANA) positivity, and hypertrophic synovitis on ultrasound confirmed the diagnosis of inflammatory arthritis compatible with juvenile idiopathic arthritis (JIA). Despite the treatment with methotrexate, arthritis progressed, and etanercept was added. The patient reached and maintained articular remission while on combined MTX and etanercept treatment during 9 years of follow-up. Case 2. A 6-year-old boy diagnosed with PWS developed arthritis of the right knee. Laboratory investigations showed mildly increased acute phase reactants, microcytic anemia, and ANA positivity at high titer (titer 1:1280). Infectious and other causes of arthritis were excluded. Ultrasound confirmed the presence of joint effusion and synovial thickening, and synovial fluid analysis was consistent with inflammatory arthrosynovitis (white blood count of 14200/µL) compatible with JIA. Shortly after the diagnosis, the ophthalmologic evaluation revealed the presence of bilateral anterior uveitis. Despite MTX and topical corticosteroid, ocular inflammation persisted and adalimumab was added. At the last follow-up, 9 months later, the child experienced inactivity of arthritis and uveitis with normal growth Conclusions: We aim to raise awareness of this possible association among pediatricians since arthritis might be underestimated due to the high pain tolerance, behavior disturbances, and the presence of other musculoskeletal abnormalities in PWS patients.